PERBANDINGAN HASIL BELAJAR ANTARA SISWA YANG DIBERI TUGAS KELOMPOK DENGAN SISWA YANG DIBERI TUGAS INDIVIDU PADA MATA PELAJARAN AQIDAH AKHLAK DI KELAS VIII MTS NEGERI 2 KUANTAN SINGINGI - Yulinda Yulinda; Sopiatun Nahwiyah; Helbi Akbar (Universitas Islam Kuantan Singingi, 2020)
Implementation of the method of giving assignments indirectly will be able to improve student learning outcomes, so also happens with the learning of the Moral Code, where the teacher gives assignments to students individually and given assignments in groups, especially students in class VIII.B and class VIII.E Problems in This research is how the comparison of learning outcomes between students who are given group assignments with students who are given individual assignments and the factors that influence them in Class VIII MTs Negeri 2 Kuantan Singingi? As subjects in this study were all students in class VIII.B who were given individual assignments and students of class VIII.E who were given assignments in groups in the field of study of the moral code of data collection by means of observation, tests, and documentation, then the final stage Data were analyzed using SPSS 20.0 From the results of data processing it can be concluded that: Comparison of learning outcomes between students who are given group assignments with students who are given individual assignments in aqidah moral subjects in Class VIII MTs Negeri 2 Kuantan Singingi is on students who are given individual assignments when the free Test is 84.08 and at the time of the Post Test was 86.52 and in the class given the group assignment when the free test was 81.98 and at the time the Post Test was 84.10. Factors that influenced the comparison of learning outcomes between students who were given group assignments with students who were given individual assignments are students who are given individual assignments more actively working on problems than students who are given group assignments, because in groups only one or two people are active, on individual assignments students are more active and work independently.